2017
DOI: 10.1634/theoncologist.2016-0241
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-Fluoropyrimidine and Paclitaxel-Based Chemotherapy in the Treatment of Advanced Anal Cancer Patients

Abstract: A platinum agent plus a fluoropyrimidine and paclitaxel-based chemotherapy are active regimens for advanced AC. Clinical trials are needed to standardize treatment pathways, investigate the potential of novel therapeutics, and improve the poor prognosis of this rare condition. 2017;22:402-408 Because of the lack of randomized trials, the optimal management of advanced anal cancer is uncertain. Despite its retrospective analysis and relatively small sample size, this is the second largest study ever conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 36 publications
(62 reference statements)
2
25
0
6
Order By: Relevance
“…More recently, a retrospective analysis of 64 patients with inoperable locally advanced SCCA showed that second‐line systemic treatment was administrated to approximately one‐third of patients after failure of a combination of platinum agent plus 5‐FU. Progression‐free survival after second‐line chemotherapy was also 3.2 months (IQR, 2.5‐7.1 months) in this case …”
Section: Discussionsupporting
confidence: 50%
“…More recently, a retrospective analysis of 64 patients with inoperable locally advanced SCCA showed that second‐line systemic treatment was administrated to approximately one‐third of patients after failure of a combination of platinum agent plus 5‐FU. Progression‐free survival after second‐line chemotherapy was also 3.2 months (IQR, 2.5‐7.1 months) in this case …”
Section: Discussionsupporting
confidence: 50%
“…At 2 years, 40% and 20% of patients in the respective groups were still alive. The increased consideration which has been given to the use of organ‐directed therapies is further confirmed by the proportion of treatment‐eligible patients who were managed with a multidisciplinary treatment approach in the two largest published retrospective series of advanced anal SCC from the Royal Marsden Hospital and the MD Anderson Cancer Center (37% and 43%, respectively) . Of note, in a further publication from the group at the MD Anderson Cancer Center the 5‐year OS of 28 patients who had undergone liver metastasectomy for SCCs (including 19 patients with anal SCC) was 47% and therefore comparable overall to the survival outcomes previously reported for colorectal cancer .…”
Section: Discussionmentioning
confidence: 90%
“…It should be noted that, while these data suggest that the magnitude of benefit deriving from organ‐directed treatments is smaller for anal SCC patients than for patients with other tumor types, they do not rule out that a multidisciplinary treatment approach may still play a role in the management of this disease. This is especially true if we consider that, despite the encouraging results of recent trials in the chemonaive and chemorefractory setting, the treatment options for advanced anal SCC patients are limited, robust management guidelines are lacking and the median overall survival is still less than 2 years . It is not surprising then that multimodality treatment strategies are increasingly adopted in routine clinical practice and reported in retrospective series (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations